Representations of Crime in New Media from the Perspective of Gamers: The Case of the GTA-V Game - Gündüz, Ömer; Nizam, Feridun (Malatya Turgut Özal Üniversitesi, 2025)
There is a wide and varied literature on the representation of crime in the media. Studies mostly focus on news content. However, crime is represented not only in news but also in many different media and content. One such channel is digital games. This study aims to reveal the forms of production and presentation of crime representations in the GTA-V game. The focus group interview technique, one of the qualitative research methods, was used in the study. The data obtained from focus group interviews with four men and four women who identified themselves as ‘gamers’ were analysed using content analysis. The research concluded that crime representations in the GTA-V game are partially similar to crime representations in traditional media and that individuals who play crime games identify with the crime scenes in the game in their real lives.

Medyada suçun temsiline ilişkin çok çeşitli ve geniş bir literatür bulunmaktadır. Çalışmalar çoğunlukla haber içeriği üzerinedir. Ancak suç, sadece haberlerde değil, birçok farklı medya ve içerikte de temsil edilmektedir. Bu kanallardan biri de dijital oyunlardır. Bu çalışmada, GTA -V oyununda suç temsillerinin üretim ve sunum biçimlerini ortaya koymak amaçlanmıştır. Çalışmada nitel araştırma yöntemlerinden biri olan odak grup görüşme tekniği kullanılmıştır. Kendilerini “gamer” olarak tanımlayan dört erkek ve dört kadınla yapılan odak grup görüşmeleri sonucunda elde edilen veriler, içerik analizi yöntemi ile analiz edilmiştir. Araştırma sonucunda, GTA-V oyunundaki suç temsillerinin geleneksel medyadaki suç temsillerine kısmen benzer olduğu ve suç oyunları oynayan bireylerin oyundaki suç sahnelerini gerçek hayatlarıyla özdeşleştirdikleri sonucuna varılmıştır.
GTA-V OYUNU ÖRNEĞİYLE GAMERLARIN GÖZÜNDEN YENİ MEDYADA SUÇ TEMSİLLERİ
Keywords: Public Administration; Kamu Yönetimi